Analisis Kelayakan Finansial pada UMKM Tahu Rahmat, Desa Kaliasri Kecamatan Kalipare Kabupaten Malang - Zahro Nisa Kamila; Rahayu Relawati (Universitas Galuh, 2026)
This study aims to analyze the financial feasibility and sensitivity of the Tahu Rahmat MSME in Kaliasri Village, Kalipare District, Malang Regency. The method used is a descriptive method with a quantitative approach. The financial feasibility analysis was carried out using Net Present Value (NPV), Gross Benefit Cost Ratio (Gross B/C), and Payback Period (PP), while a sensitivity analysis was carried out on the increase in labor costs and the decrease in benefits. The results of the study indicate that the Tahu Rahmat MSME is feasible to run based on the NPV value of Rp 17,766,591,044, Gross B/C of 1.57, and PP for 0.13 years or equivalent to approximately 1 month 15 days. The sensitivity analysis shows that a 20% increase in labor costs reduces the NPV by 5.7%, while a 20% decrease in benefits reduces the NPV by 55.2%. However, the NPV value in both conditions is still positive so the business remains feasible to run. The results also show that the Tahu Rahmat MSME is more sensitive to decreases in benefits than increases in labor costs.